2007
DOI: 10.1073/pnas.0703868104
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy and perceptual distortions in absolute pitch ability

Abstract: Absolute pitch (AP) is the rare ability to identify the pitch of a tone without the aid of a reference tone. Understanding both the nature and genesis of AP can provide insights into neuroplasticity in the auditory system. We explored factors that may influence the accuracy of pitch perception in AP subjects both during the development of the trait and in later age. We used a Web-based survey and a pitch-labeling test to collect perceptual data from 2,213 individuals, 981 (44%) of whom proved to have extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
158
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(175 citation statements)
references
References 19 publications
17
158
0
Order By: Relevance
“…If the replication failed with humans, then we need to develop a more effective procedure for testing humans: one that takes pitch height into account and can also be adapted for training birds. Humans with absolute pitch (AP) can usually identify the chroma of a pitch across octaves, so we prescreened the participants to identify AP possessors using a note-naming test (Athos, Levinson, Kistler, Zemansky, Bostrom, Freimer, & Gitschier, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the replication failed with humans, then we need to develop a more effective procedure for testing humans: one that takes pitch height into account and can also be adapted for training birds. Humans with absolute pitch (AP) can usually identify the chroma of a pitch across octaves, so we prescreened the participants to identify AP possessors using a note-naming test (Athos, Levinson, Kistler, Zemansky, Bostrom, Freimer, & Gitschier, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was adapted from a procedure used by Athos et al (2007) to test 2,213 participants: The note durations and frequencies were a direct replication of Athos et al's procedure. In the note-naming tests, we identified AP possessors using Athos et al's scoring protocol: 1 point for each correct identification, and 0.75 points for responses to notes ±1 semitone from the correct note.…”
Section: Ap Testingmentioning
confidence: 99%
“…The authors found that AP individuals designated a much broader range of frequencies as ''A'' than was the case for other notes. Athos et al (2) suggest that this odd phenomenon may be explained by the fact that not all modern orchestras tune to 440 Hz. Some, particularly in Europe, tune to slightly higher frequencies, such as 442 or even 446 Hz.…”
Section: A Distinct Groupmentioning
confidence: 99%
“…Athos et al (2) report results from an unusually large group of AP subjects, recruited and evaluated through an interactive web site that provided information on Ͼ2,000 individuals. Their results are both surprising and significant.…”
Section: A Distinct Groupmentioning
confidence: 99%
See 1 more Smart Citation